Hypoxia-inducible factor-1alpha protects the liver against ischemia-reperfusion injury by regulating the A2B adenosine receptor. Issue 1 (1st January 2021) - Zhang, Xingjian; Du, Peng; Luo, Kaifeng; Li, Yong; Liu, Zhongzhong; Wang, Wei; Zeng, Cheng; Ye, Qifa; Xiao, Qi
ABSTRACT: Hepatic ischemia-reperfusion injury (IRI) is an inevitable complication associated with liver surgical procedures, and its pathological process remains elusive. Therefore, the present study investigated the role and mechanism of hypoxia-inducible factor-1alpha (HIF-1α) in hepatic IRI. Here, we constructed rat models with hepatic IRI and BRL-3A cell models with hypoxia/reoxygenation (H/R) insult. The extent of liver injury was assayed by measuring serum ALT/AST levels and performing H&E staining; the levels of SOD, MDA, MPO, IL-6 and TNF-α were determined using commercial kits; apoptosis was detected using the TUNEL assay and flow cytometry; and the expression of HIF-1α/A2BAR signaling-related molecules and apoptosis-associated indicators was detected using Western blotting or qRT-PCR. The expression level of HIF-1α was significantly upregulated in the liver of rats subjected to IRI, as well as in BRL-3A cells treated with H/R. HIF-1α overexpression exerted a protective effect on hepatic IRI or H/R insult by reducing serum aminotransferase levels and hepatic necrosis, inhibiting inflammation and apoptosis of hepatocytes, and alleviating oxidative stress. In contrast, inhibition of HIF-1α expression exacerbated hepatic injury induced by IR or H/R. Mechanistically, the expression level of A2BAR was markedly increased during hepatic IRI or H/R insult. Moreover, A2BAR expression increased with HIF-1α upregulation and decreased with HIF-1α downregulation. Importantly, inhibition of A2BAR signaling abolished HIF-1α overexpression-mediated hepatoprotection. Taken together, HIF-1α exerts protective effects on hepatic IRI by attenuating liver necrosis, the inflammatory response, oxidative stress and apoptosis, and its mechanism may be related to the upregulation of A2BAR signaling. GRAPHICAL ABSTRACT: uf0001 Graphical abstract: